Mind Mapping in a Collaborative Learning Model: Strengthening Link-and-Match (8+i) Partnerships in Center of Excellence Vocational Schools - Mawarda Nurodanika; Gunadi Gunadi (MAN 4 Kota Pekanbaru, 2026)
This study examines the use of mind mapping in a collaborative learning model to strengthen Link-and-Match (8+i) partnerships in a Center of Excellence vocational school. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and document analysis involving school leaders and productive teachers in the Light Vehicle Engineering program at SMK Bhakti Loa Janan, Kutai Kartanegara, Indonesia. The findings show that mind mapping functions as an analytical and collaborative tool to visualize key partnership components, including curriculum alignment, guest teachers, internships (PKL), competency certification, teaching factory, and graduate absorption. The mapped analysis reveals that while partnerships with industry are established through MoUs and several programs have been implemented, gaps remain in the consistent application of project-based learning (PjBL), teaching factory utilization, technology updates, and teacher capacity building. Mind mapping supports stakeholders in identifying implementation gaps and prioritizing improvements to enhance the sustainability and effectiveness of industry collaboration in vocational education.